Survey on public health risks at artisanal brick kilns in Kananga City (Central Kasaï Region), Democratic Republic of the Congo - Ngemale, D. M.; Kabombo, M. F.; Matand, T. A.; Musenga, T. V.; Monizi, M.; Djolu, R. D.; Masengo, A. C.; Ngbolua, K. N. (Orapuh Journal, 2024)
Introduction In developing countries, diseases related to unsafe water, a lack of sanitation, and poor hygiene are important (famous) public health challenges. Purpose This study aimed to survey the public health risks at artisanal brickworks in the city of Kananga, Democratic Republic of the Congo. Methods A prospective survey was carried out among artisanal brickmakers and brickworks using questionnaires and free observation. Results The study revealed that 58% of brickyards used river water, 35% used marsh water, and 8% used pond water to shape bricks, so there was no safe water source at brick yards. Of these water sources, 84% drink unsanitary water from rivers and lakes, 23% store water in an open container, 25% drink from the source at any time when they are thirsty, 90% drink only once a day after eating or washing, 71.5% wash only once a day after working, and 5% rarely wash; 100% of people do not clean the clothes they use at work regularly; 83% of people do not have appropriate clothing for their work. They don’t have boots or gloves and work with their hands and naked feet. 95.5% of bricklayers sleep in the surrounding bush. Conclusion These observations sufficiently prove that in brick factories, sanitation and hygiene measures are defective or even inadequate, and brick manufacturers are prone to various environmental diseases, of which lack of sanitation and hygiene are the main causes. This study thus highlights practices that are related to brick manufacturing, endangering public health through the contamination of drinking water and contributing to environmental problems such as deforestation. Material support, supervision of contractors for sanitation and hygiene, and health education in brick yards are recommended for promoting environmental sanitation and hygiene.